Human Resource Development to Improve Competitive Advantage in the Digital Era - Farand Qolbi Urdha; Farel Ramadhan; Adli Al Ghani; Dian Prihardini Wibawa (ITQAN: Journal of Islamic Economics, Management, and Finance, 2026)
The purpose of this study is to analyze human resource development strategies to enhance organizational competitive advantage in the digital era. This study uses a qualitative method with a literature review approach. The analysis then focuses on HR development strategies. The results of this study indicate that the combination of competency-based training strategies, structured recruitment, leadership development, and the implementation of digital technology in HR management is a determining factor in creating organizational competitive advantage. This study has presented a holistic framework that integrates traditional HR development strategies with digital transformation. The results of this study guide management practitioners and policymakers in formulating adaptive and sustainable HR development strategies by integrating digital technology in every aspect of HR management.